Implementasi Learning Management System untuk Mendukung Pembelajaran Jarak Jauh Sekolah Menengah Kejuruan - Iqbal Santosa; Ryan Adhitya Nugraha (Universitas Lancang Kuning, 2022)
Around 19.8 million high school children in Indonesia are currently studying under the threat of the COVID-19 pandemic. To prevent the transmission of the COVID-19 in the school environment, the Minister of Education and Culture has issued a circular letter regarding online learning and work from home, which requires all schools to implement the “Learn from Home” policy. This policy must be applied from the new semester of 2020-2021 and needs to be supported by a Learning Management System (LMS) along with the competence of all stakeholders. Moodle was chosen because it is free, customizable, and can be deployed in a dedicated server to be fully managed by the school. Implementation stages include requirements gathering, installation and configuration, testing, training, and evaluation. The evaluation noted some needs for the next program, such as simplifying the input process for quiz questions, exploring deeper features, and providing more informative tutorials.